2020
DOI: 10.3390/microorganisms8121982
|View full text |Cite
|
Sign up to set email alerts
|

Marine Bacteria Display Different Escape Mechanisms When Facing Their Protozoan Predators

Abstract: Free-living amoeba are members of microbial communities such as biofilms in terrestrial, fresh, and marine habitats. Although they are known to live in close association with bacteria in many ecosystems such as biofilms, they are considered to be major bacterial predators in many ecosystems. Little is known on the relationship between protozoa and marine bacteria in microbial communities, more precisely on how bacteria are able survive in environmental niches where these bacterial grazers also live. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 96 publications
1
12
0
Order By: Relevance
“…While the molecular basis of the observed bacterial responses and the involved cues are unknown, our results suggest that habitat shifts are key to escape high predation pressure and allow for bacterial persistence. Our results are in line with laboratory experiments by [ 24 ] revealing similar escape behavior of four different surface-attached bacteria in the presence of a surface predator—the amoeba A. castellanii . They found that even the liquid supernatant of the A. castellanii culture induced the bacterial escape response, pointing to the fact that chemical signaling may trigger the bacterial behavior.…”
Section: Discussionsupporting
confidence: 92%
“…While the molecular basis of the observed bacterial responses and the involved cues are unknown, our results suggest that habitat shifts are key to escape high predation pressure and allow for bacterial persistence. Our results are in line with laboratory experiments by [ 24 ] revealing similar escape behavior of four different surface-attached bacteria in the presence of a surface predator—the amoeba A. castellanii . They found that even the liquid supernatant of the A. castellanii culture induced the bacterial escape response, pointing to the fact that chemical signaling may trigger the bacterial behavior.…”
Section: Discussionsupporting
confidence: 92%
“…We should add, though, that such a dilemma (between escape from ingestion and resistance to digestion) is not the only trade-off that microbes face due to grazing pressure. For example, it is well known that bacteria can form biofilms or clumping ( 39 , 40 ) to avoid capture by protists at the expense of growth, with such morphological changes affecting cell-surface area-to-volume ratios, which negatively impact on nutrient uptake for optimum growth. Similarly, unicellular algae with larger cell sizes are poorly grazed, but have low ammonium uptake rates and grow poorly ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, the samples were directly fixed by adding formaldehyde at 4% (vol/vol) for 20 min, and a low-speed centrifugation (15 min at 900 × g ) was used to initiate and increase cell adhesion to the coverslips. Finally, cells were stained with DAPI (5 μg/mL) and ConA TRITC conjugate (20 μg/mL; Thermo Fisher Scientific) ( 39 ) and mounted with a drop of Mowiol antifade before observation using a confocal laser scanning microscope (CLSM; Zeiss LSM 880). Bacterial biovolumes and the biovolume of ConA-stained glycoconjugates in CLSM images were determined by using five images for each of the three replicates using COMSTAT software developed in MATLAB R2015a (MathWorks), as described ( 64 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predation by protozoa is a major selective force acting on bacterial populations, producing a variety of predation avoidance mechanisms ( 1 , 2 ); assembling into bigger and harder to swallow multicellular structures ( 3 ), swimming away from a predator ( 4 ), producing antipredator toxins ( 5 ), interfering with predator phagocytosis and digestion processes, and modulating cell surfaces to evade predator recognition ( 6 ).…”
Section: Introductionmentioning
confidence: 99%